Analysis Of The Views of Kiai NU and Muhammadiyah in Bangkalan Madura Regarding The Use of Bitcoin as A Means of Payment of Zakat - Fatimatus Zahroh; Layyin Mahfiana (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2023)
This study aims to find out the views of NU and Muhammadiyah kiai in Bangkalan Madura related to Bitcoin law and zakat payment law with Bitcoin. This research was motivated because the pros and cons related to the use of Bitcoin and zakat payments using Bitcoin money until now are still a discussion of scholars until the kiai in Bangkalan Madura also differ in opinion regarding the Bitcoin law, where most of the kiai NU and Muhammadiyah Bangkalan related to Bitcoin law and zakat law with Bitcoin declare haram, because it contains elements of gharar (obscurity ), maysir (gambling), as well as the absence of official regulation from the government. Therefore, zakat with Bitcoin is not allowed. However, there are some scholars who state that the digital money law is halal because digital money like crypto is classified as a "virtual treasure" thus it applies mandatory zakat to Bitcoin money. In addition, there are also differences in regulations between the government and BAPPEBTI, where the government states in Law No. 7 of 2011 concerning currency that it does not accept payment instruments other than Rupiah, while in BAPPEBTI regulations provide protection for Bitcoin users so as not to feel losses. However, obeying government rules is mandatory.